Morphological and molecular characterisation of Scutellonema species from yam (Dioscorea spp.) and a key to the species of the genus - Kolombia, Y.A.; Karssen, G.; Viaene, N.; Kumar, P. Lava; Joos, L.; Coyne, Danny L.; Bert, W. (Brill, 2017)
The yam nematode, Scutellonema bradys, is a major threat to yam (Dioscorea spp.) production across yam-growing regions. In West Africa, this species cohabits with many morphologically similar congeners and, consequently, its accurate diagnosis is essential for control and for monitoring its movement. In the present study, 46 Scutellonema populations collected from yam rhizosphere and yam tubers in different agro-ecological zones in Ghana and Nigeria were characterised by their morphological features and by sequencing of the D2-D3 region of the 28S rDNA gene and the mitochondrial COI genes. Molecular phylogeny, molecular species delimitation and morphology revealed S. bradys, S. cavenessi, S. clathricaudatum and three undescribed species from yam rhizosphere. Only S. bradys was identified from yam tuber tissue, however. For barcoding and identifying Scutellonema spp., the most suitable marker used was the COI gene. Additionally, 99 new Scutellonema sequences were generated using populations obtained also from banana, carrot, maize and tomato, including the first for S. paralabiatum and S. clathricaudatum, enabling the development of a dichotomous key for identification of Scutellonema spp. The implications of these results are discussed.